THE ART OF CHARACTER CREATION IN ABDULLA JABBOR’S DRAMATIC WORKS - Mirzajonova Shaxnozakhon Ne’matjon qizi (Modern American Journals, 2025)
This article examines the dramaturgical heritage of Abdulla Jabbor, one of the leading representatives of the Namangan literary environment. The author analyzes the thematic diversity, artistic expression, and national values reflected in Jabbor’s dramatic works. The study focuses on his contribution to the development of modern Uzbek drama, highlighting his philosophical approach, social ideas, and patriotism. It also explores the influence of historical and moral themes on the formation of his creative worldview. The results demonstrate Abdulla Jabbor’s unique position in shaping the ideological and aesthetic foundation of Namangan’s literary life.
Keywords: Abdulla Jabbor, dramaturgy, Uzbek literature, Namangan literary environment, artistic expression, patriotism, philosophy.